Communication Process In Second Language Acquisition Influenced By General Factors - Waode Hamsia (JUPE : Jurnal Pendidikan Mandala, 2019)
In communication process, there were some students who faced some problems in expressing their ideas in speaking English as the second language acquisition. The problems are especially in applying expression, choosing words, and lacking of vocabularies. The problem in applying expression was caused by an interruption and a lack of preparation. Then the next problem in choosing words was caused by the difficulties to find some approriate words and using in a grammatically correct sentences. The last in lacking of vocabularies was caused by having a few vocabularies. The purpose of this researh analyzed the communication process in second language acquisition that employed by the students. The strategies that used in communication process were influenced by some general factors.  The method used a qualitative research. The data were the students’ verbal and non verbal language. The instruments were observation and interview. The subjects were the students in English program who were in the fourth semester in Muhammadiyah University of Surabaya. The result showed there were eight communication strategies proposed by littlewood to solve the problems in speaking English. The communication strategies used by the students were influenced by some general factors. The factors are proficiency level, problem source, personality and learning situation.  Therefore the students could maintain the conversation successfully.